Safety-Enhanced Model-Free Visual Servoing for Continuum Tubular Robots Through Singularity Avoidance in Confined Environments - Wu, K. (Institute of Electrical and Electronics Engineers Inc., 2021)
10.1109/ACCESS.2019.2891952